Positronics of subnanometer atomistic imperfections in solids as a high-informative structure characterization tool - Shpotyuk, Oleh (Nanoscale Res Lett, 2015)
Methodological possibilities of positron annihilation lifetime (PAL) spectroscopy applied to characterize different types of nanomaterials treated within three-term fitting procedure are critically reconsidered. In contrast to conventional three-term analysis based on admixed positron- and positronium-trapping modes, the process of nanostructurization is considered as substitutional positron-positronium trapping within the same host matrix. Developed formalism allows estimate interfacial void volumes responsible for positron trapping and characteristic bulk positron lifetimes in nanoparticle-affected inhomogeneous media. This algorithm was well justified at the example of thermally induced nanostructurization occurring in 80GeSe(2)-20Ga(2)Se(3) glass.